The Influence of Cashless Society and Financial Literacy on Gen Z's Consumptive Behavior with Self-Control as an Intervening Variable - Dewi, Cahaya Maulida; Hana, Kharis Fadlullah (Universitas Muhammadiyah Sumatera Utara, 2025)
The increasing use of digital transactions among students encourages more practical financial patterns, but is prone to triggering consumptive behavior. Meanwhile, financial literacy that has not been fully implemented is an obstacle in controlling the urge to digital consumption. This study aims to analyze the effect of cashless society and financial literacy on consumptive behavior with self-control as an intervening variable. The quantitative descriptive associative research approach using SEM-PLS on FEBI UIN Sunan Kudus Students. The results of the study indicate that cashless society has a positive and significant effect on consumptive behavior, while financial literacy does not have a significant effect on consumptive behavior. Cashless society also does not affect self-control, but financial literacy has a positive effect on self-control. Self-control has a positive effect on consumptive behavior and mediates the effect of financial literacy on consumptive behavior, but does not mediate the effect of cashless society on consumptive behavior. Further research is recommended to expand the scope of the population and respondent area, use a mixed methods approach, and add other variables.